Growth Performance Characteristics of Goats Fed Varied Levels of Poultry Manure in whole Cassava Plant Based Concentrate Diet - M. B, Yousuf; A. A, Adeloye; K. M, Okukpe; K. D , Adeyemi; Badmus , A. H. A; J. O, Daramola; N. J, Ogundun (Asian Journal of Agriculture and Rural Development, 2013)
A 56-day feed intake, growth and digestibility trial was carried out to investigate the use of poultry manure as a fermentable nitrogen source in whole cassava plant-based concentrate fed to goats on basal Panicummaximum hay (9.18 % CP). Sixteen adult (2 years old; 12.48 – 16.72 kg initial body weights) West African Dwarf goats were blocked on the basis of body weights into four similar groups that were assigned randomly to four treatments. Treatments consisted of dried poultry manure that was included in a cassava-based concentrate at 0, 14, 18 or 22 % level. Average feed intake (g/W0.725 kg) was reduced (p < 0.05) in goats fed poultry manure at 22 % inclusion level when compared with the other dietary groups. Effects of poultry manure treatments on digestibility of dry matter or crude protein, nitrogen retention and body weight gain were significant (p < 0.05). It was concluded that poultry manure could be used to complement cassava leaf meal in cassava plant-based concentrates for the goats. The use of poultry manure as a source of fermentable nitrogen would promote activities of rumen microbial populations for efficient fermentation and reduce the constraints associated with collection and processing of cassava leaf in sufficient quantity for inclusion in the diet.